Rheology of methane hydrate slurries formed from water-in-oil emulsions - Webb, Eric B. (Colorado School of Mines. Arthur Lakes Library, 2007)
2014 Spring. Includes illustrations (some color). Includes bibliographical references (pages 144-153). Solid structures known as natural gas hydrates can form in subsea pipelines, hindering and sometimes blocking flow completely. A knowledge of the flow properties of hydrate containing slurries could help the oil industry better predict and prevent hydrate formation. In particular, the rheology (e.g., viscosity, yield stress) of hydrate slurries is not well understood. On a more scientific level, the transient rheological properties of an emulsion converting to a suspension has not been studied extensively. A high pressure rheometer apparatus was developed to study hydrate formation from water-in-oil emulsions. This study conducted investigations on three different emulsions from which hydrates were formed: water-in-West African crude oil (a fluid found in subsea pipelines), water-in-dodecane with AOT surfactant (a model emulsion with low viscosity), and water-in-70T mineral oil with span 80 and AOT surfactants (a model emulsion with high viscosity). Each of these emulsions provides a unique way to observe hydrate rheology. In every emulsion, viscosity increased on the order of minutes upon hydrate formation. Hydrate formation from water-in-oil emulsions increased viscosity, increased shear-thinning behavior, and introduced a yield stress to the original emulsion. The transient viscosity profile as hydrate form and grow were influenced by many factors including conversion of liquid water drops to solid particles, aggregation of hydrate particles, methane depletion and diffusion, and capillary bridging. In the mineral oil-based system, methane saturated emulsion viscosity was about an order of magnitude larger than methane saturated mineral oil viscosity. The maximum viscosity observed during hydrate formation was on the order of a 10-fold increase in viscosity. So, introduction of water to oil in a pipeline followed by hydrate formation may cause a 100-fold increase in viscosity. Fractional conversion of water to hydrate was calculated from pressure measurements. Hydrate slurry viscosity reached a maximum at less than 100% conversion of water to hydrate; so, viscosity of this part-suspension-part-emulsion was higher than suspension or emulsion viscosity. In the dodecane and mineral oil-based emulsions, if significant unconverted water remained after the initial formation event, viscosity increased for a time as additional methane dissolved and converted some remaining water to hydrate. In general, decreased driving force (e.g., temperature) for hydrate formation resulted in increased rheological properties (transient viscosity, yield stress, steady state viscosity).